“GEOLOGI DAERAH BAILANG DAN SEKITARNYA, MANADO PROVINSI SULAWESI UTARA” - Dote, Mesak; Masulili, Febryanto (LPPM Universitas PRISMA, 2025)
This study aims to understand the geological conditions of the Bailang area and its surroundings, located in Bunaken District, Manado City, North Sulawesi Province, through surface geological mapping at a 1:25,000 scale. The methods used include direct observation, field measurement, and analysis of geomorphology, stratigraphy, geological structure, and geological history. The study area is situated at coordinates 1˚33ˈ54.98˝ N and 124°50ˈ42.87˝ E, covering an area of 49 km². The geomorphology of the study area is divided into six subunits: Residual Hills, Isolated Hills, Dissected Volcanic Hills, Volcanic Foot, Volcanic Footplain, and Volcanic Fluvial Plain. The geological structure analysis reveals the presence of primary structures with a dominant northwest–southeast orientation. The stratigraphy consists of four rock units: the Pandu–Molas Andesite Lava Unit (Pleistocene–Holocene), the Molas Breccia Unit (Pleistocene), the Bailang Tuff Unit (Quaternary), and the Alluvial Unit (Holocene). These units formed through four geological phases reflecting volcanic activity from Mount Tumpa and fluvial sedimentation processes. The research outcomes include geological, geomorphological, and traverse maps that illustrate the geological framework of the area. This information is expected to support a deeper understanding of the regional geological evolution of North Sulawesi and provide valuable insights for spatial planning and local natural resource management. Keywords: geological mapping, geomorphology, stratigraphy, geological structure, Bailang.